Perspektif Remaja Hindu Terhadap Ajaran Catur Varna dan Sistem Kasta pada Zaman Modern di Desa Sukamaju - Sintia, Ni Kadek (Satya Widya: Jurnal Studi Agama, 2025)
Hinduism is a teaching based on the Vedas and upholds the principle of sanatana dharma (eternal truth). Hindu social life is based on moral teachings that prioritize peace and harmony in life. However, the blurring of the values of the catur varna teaching as one of the foundations of Hindu morality and equating the catur varna teaching with the caste system (social stratification) causes various Hindu youth perspectives on these two concepts. Thus, this study seeks to describe the perspectives of Hindu adolescents on the teachings of catur varna and the caste system, analyze the causes of perspective errors, and examine efforts that can be made to straighten out misunderstandings. This research is qualitative research with case study method. Data were collected through observation, interviews, and documentation studies. The data collected was then analyzed using Miles and Huberman's data analysis which consists of data reduction, data display, and data verification. The results of this study show that Hindu teenagers have various views on the teachings of chess varna and the caste system. But in general, teenagers have a misunderstanding of the teachings of chess varna and there is a blurring of the meaning and values of the teachings of chess varna into a caste system. The misunderstanding of this concept is caused by various internal and external factors of Hindu adolescents. The efforts to overcome the misunderstanding include the integration of catur varna learning in education, community development, utilization of social media, and the role of family and religious leaders.